Perancangan Robot Pembersih Vacuum Pintar Berbasis Mikrocontroller Menggunakan Android - Leonardo Silalahi; Zelvi Gustiana; Zulham . (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
Robotics innovation has experienced rapid advancements, bringing significant changes to robots, enabling them to adapt to innovative environments. Integrated control systems with microcontrollers and Android platforms facilitate human tasks. Robots are also beneficial in flexible situations such as clinics, homes, workplaces, and hazardous areas. One practical application is the floor-cleaning device with Android control system. In its implementation, the program utilizes the Arduino Uno IDE integrated with a microcontroller. This floor-cleaning device effectively removes dust and dirt. The research on